Pelvic Lymph Node Dissection in Prostate Cancer: Is It Really Necessary? A Multicentric Longitudinal Study Assessing Oncological Outcomes in Patients With Prostate Cancer Undergoing Pelvic Lymph Node Dissection vs Radical Prostatectomy Only - Furrer, Marc A; Sathianathen, Niranjan J; Mulholland, Clancy J; Papa, Nathan; Katsios, Andreas; Soliman, Christopher; Lawrentschuk, Nathan; Peters, Justin S; Zargar, Homi; Costello, Anthony J; Hovens, Christopher M; Liodakis, Peter; et al. (The Journal of urology, 2025)
With the availability of prostate-specific membrane antigen positron emission tomography scans, it is controversial whether pelvic lymph node dissection (PLND) at the time of radical prostatectomy (RP) is still the most reliable and accurate staging modality for lymph node assessment. Furthermore, the oncological benefit of PLND remains unclear. The aim of this study was to assess whether omitting PLND in patients undergoing RP for prostate cancer (PCa) is associated with the risk of tumor recurrence and progression to metastasis. In this longitudinal multicenter cohort study, we reviewed data of 2346 consecutive patients with PCa who underwent RP with (n = 1650) and without (n = 696) extended PLND between January 1996 and December 2021. Recurrence-free survival and metastasis-free survival (MFS) were analyzed as a time-to-event outcome using Kaplan-Meier analyses with log-rank tests. To assess the effect of PLND, we created multivariable Cox proportional hazards models adjusting for relevant clinical and demographic characteristics. Median follow-up was 44 months. There was no difference in recurrence-free survival between men who had a PLND and those who did not (HR, 1.07, 95% CI, 0.87-1.32, = .52). Patients with D'Amico high-risk disease (PSA >20 µg/L and/or International Society of Urological Pathology grade group ≥4) demonstrated a significantly prolonged MFS if they underwent PLND (HR, 0.57, 95% CI, 0.36-0.91, = .02). PLND also improved MFS in patients with intermediate-risk disease (HR, 0.48, 95% CI, 0.25-0.90, = .023). Further significant prognostic variables for MFS on multivariable Cox proportional hazards regression were PSA, International Society of Urological Pathology grade group, and pathological T-stage. PLND improves MFS in patients with D'Amico intermediate-risk and high-risk PCa and may therefore be considered in men undergoing RP.